2021
DOI: 10.33215/sjom.v4i4.683
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Contract Fulfillment and Attitude towards Organizational Change: A Mediation and Moderation Analysis of Affective Commitment and Empowering Leadership

Abstract: Purpose: The underlying factors connecting psychological contract fulfillment (PCF) to attitude towards organizational change (ATOC) have not received much attention in organizational behavior literature. Hence, this study examined the mediating role of affective commitment (AC) and the moderating role of empowering leadership (EL) in the relationship between PCF and ATOC among employees in private organizations. Design/Methodology: This is a quantitative cross-sectional survey. Systematic sampling was utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Through the behaviors of empowering leaders (e.g., enhancing work meaningfulness, providing autonomy, and ensuring participation in decision-making), employees can easily adapt to the work environment as a result of these experiences. 34,40 A positive psychological state is a necessity for the experience of well-being at work. An employee in a positive psychological state shows optimism and resilience, which in turn translate to well-being at work.…”
Section: Discussionmentioning
confidence: 99%
“…Through the behaviors of empowering leaders (e.g., enhancing work meaningfulness, providing autonomy, and ensuring participation in decision-making), employees can easily adapt to the work environment as a result of these experiences. 34,40 A positive psychological state is a necessity for the experience of well-being at work. An employee in a positive psychological state shows optimism and resilience, which in turn translate to well-being at work.…”
Section: Discussionmentioning
confidence: 99%
“…These empirical findings are also reinforced by the social exchange theory (Blau, 1964), where employees are motivated to return organizational support through positive work behaviors. Edosomwan et al (2020) found that investing in workers' employability can promote a positive attitude in the organization if it is adequately done through the social exchange process. Based on the empirical literature and theoretical support discussed above, it is hypothesized that: H2: Perceived organizational support will moderate the relationship between perceived employability and sabotage behavior such that the relationship will be stronger among workers with low perceived organizational support.…”
Section: Perceived Organizational Support As Moderator Of the Stated ...mentioning
confidence: 99%
“…Through adequate social exchange relationships, organizations can invest in employability through extensive programs and training that promote employability skills because the organization stands to gain from employees who can carry out their job effectively. Investing in employability can positively affect the organization if conducted through the social exchange process (Akkermans et al, 2019;Edosomwan et al, 2020). Hence, investing in employability can provide a sense of obligation on the part of the employee towards the organization.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Several antecedents of constructive deviance have been explored, some of which include work-family enrichment (Khan & Rehman, 2019), empowering leadership (Mertens & Recker, 2020), organizational justice, and psychological contract breach (Cohen & Ehrlich, 2019;Gong et al, 2021), group citizenship behavior, and environmental dynamism (Liu et al, 2020), workplace spirituality (Garg & Saxena, 2020), and Knowledge sharing system (Malik & Malik, 2021). Recent reports suggest that perceived organizational support (POS) and other exchange variables, such as psychological contract fulfillment and organizational justice, are linked to behaviors that benefit the organization (e.g., Afsar & Badir, 2016;Cohen & Ehrlich, 2019;Edosomwan & Nwanzu, 2021;Kura et al, 2016). Consequently, this study utilizes POS as a predictor variable.…”
Section: Introductionmentioning
confidence: 99%